Surface Water Purification for Drinking Purposes Using Mechanical Mixing - صبوح حسام; جبيلي علياء (Latakia University Journal -Engineering Sciences Series, 2021)
The coagulation and flocculation are considered one of the most important processes for drinking water purification from surface sources, so the aim of this research is to study the parameters affecting the coagulation and flocculation processes represented by the velocity gradient and time for each one, for samples of raw water (turbidity removing) from Lake ’’16 Tishreen’’ Dam by mechanical mixing. Then determine the optimal values of these parameters depend on the raw water turbidity that using in the experiments. Experiments were conducted on water samples with different raw turbidity( 50-100-150-200-250-300 mg/l) using aluminum sulfate [ ] as a coagulant after determining the optimal dose value for each Turbidity using the experimental coagulation device (Jar- Test).The results showed that the optimal values ​​of the coagulation, flocculation time were (T1 = 35 – 50 sec ) , ( T2 = 840 – 1080 sec ) while The optimum value of velocity gradient was (G1 = 225 – 275 sec-1), ( G2 = 40 – 55 sec-1) for each turbidity in the experimental work. The results proved that mechanical mixing is an effective treatment technology for surface water purification where the residual turbidity didn’t exceed the limits allow water to flow into the filters in order to remove her residual turbidity. It was ( 8 – 15 mg/l) at the optimal parameters.